Costly Giving, Giving Guaízas : Towards an organic model of the exchange of social valuables in the Late Ceramic Age Caribbean. - Mol, Angenitus Arie Andries, 1984- (Sidestone Press, 2006)
An Archaeology of Exchange is primarily an archaeology of human sociality and anti-sociality. Nevertheless, archaeological studies of exchange are numerous and varied, and archaeologists do not always approach exchange as a social mechanism, concentrating rather on the cultural, economic or political implications of exchange. Even so, at times it is worth retracing the implicit theoretical steps that archaeologists have taken and look at human sociality through the eyes of exchange as something new. This is undertaken here by concentrating on the exchange of social valuables in the later part.